Metabolites-mitochondria-macrophages (MMM): new therapeutic avenues for inflammation and muscle atrophy - Angelini, Corrado (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Mills et al. (1) have published an important article to demonstrate that upon lipopolysaccharide (LPS) stimulation, macrophages in mice change to a pro-inflammatory state, producing ATP instead by oxidative phosphorylation (OX-PHOS) to glycolysis pathway. They demonstrate that increased mitochondrial oxidation of succinate through succinate dehydrogenase (SDH) brings high mitochondrial membrane potential and increases production of reactive oxygen species (ROS). Blocking ROS production with rotenone, a complex I inhibitor and uncoupling mitochondria, results in an inhibition of this macrophagic pro-inflammatory phenotype. Also, expressing alternative oxidase, which inhibits the inflammatory phenotype, protects mice from LPS lethality.